Sustainable Biogenic Synthesis of High-Performance CaO/NiO Nanocomposite for Antimicrobial, Antioxidant, and Antidiabetic Applications - Saravanan Priyadharshini; Muniappan Ayyanar; Ravichandran Krishnasamy; Manimaran Sundarraj; Gabriela Sandoval-Hevia; Arun Thirumurugan; Natarajan Chidhambaram (Ceramics, 2025)
Herein, we present in-depth investigations of the biological activities of a CaO/NiO nanocomposite synthesized via a sustainable eco-friendly approach, utilizing Citrus limonium fruit extract as a natural stabilizing and facilitating agent. The efficacy of the nanocomposite is compared with those of individual CaO and NiO nanoparticles. X-ray diffraction analysis confirms the cubic phase of CaO as well as NiO within a unified matrix, demonstrating a refined crystallite size of 48 nm, which is smaller than that of the individual nanoparticles. FTIR study substantiates the occurrence of strong Ca-O-Ni-O bonds, along with CO32−, C–H, and CH2 bonds. The CaO, NiO, and CaO/NiO samples exhibit bandgap values of 1.70, 3.46, and 3.44 eV, respectively. Surface morphology analysis reveals that CaO/NiO holds a well-defined heterostructure with porous morphology. An XPS study confirms that Ca and Ni elements exist in the 2+ oxidation state in the CaO/NiO. The nanocomposite exhibits superior antibacterial activity, with inhibition zones of 24.3 mm against Bacillus subtilis and 20.6 mm against Salmonella typhi, and MIC values of 23.4 and 46.8 µg/mL, respectively. It also demonstrates strong antioxidant potential, with IC50 values of 96.8 ± 0.4 µg/mL (DPPH) and 91.8 ± 0.1 µg/mL (superoxide anion). Furthermore, it shows the lowest IC50 for α-amylase (98.6 ± 0.7 µg/mL) and strong α-glucosidase inhibition (81.96 ± 0.5 µg/mL). Consequently, this insightful study reveals how biogenic synthesis helps develop high-performance multifunctional CaO/NiO nanocomposites for biomedical applications.